Asymmetric synthesis of a high added value chiral amine using immobilized ω-transaminases - Petri, Antonella; Colonna, Valeria; Piccolo, Oreste (Beilstein Journal of Organic Chemistry, 2019)
Chiral N-heterocyclic molecules and in particular compounds with an amino functional group such as 3-aminopiperidine are valuable intermediates for the production of a large number of bioactive compounds with pharmacological properties. In this paper, the synthesis of both enantiomers of 3-amino-1-Boc-piperidine by amination of the prochiral precursor 1-Boc-3-piperidone using immobilized ω-transaminases (TAs-IMB), isopropylamine as amine donor and pyridoxal-5’-phosphate (PLP) as cofactor is described. Compared to other methods, the present approach affords the target compound in just one step with high yield and high enantiomeric excess starting from a commercial substrate. The reaction was carried out by using different commercially available immobilized enzymes, evaluating the catalytic activity and the enantioselectivity under different experimental conditions. Re-use of the most efficient enzyme was performed both in batch and in a semi-continuous system. The selected biocatalyst showed good stability under the reaction conditions providing consistent results in terms of conversion and enantiomeric excess after several cycles. The reported results may be of practical interest in view of the development of this sustainable approach to an industrial scale.
Keywords: asymmetric catalysis; biotransformations; chiral amine; immobilized enzymes; ω-transaminases